2021
DOI: 10.1038/s41598-021-82702-6
|View full text |Cite
|
Sign up to set email alerts
|

No evidence that monkeys attribute mental states to animated shapes in the Heider–Simmel videos

Abstract: Human Theory of Mind (ToM) is so automatic and pervasive that we spontaneously attribute mental states to animated abstract shapes, as evidenced by the classic Heider–Simmel findings. The extent to which this represents a fundamental characteristic of primate social cognition is debated. Prior research suggests that monkeys spontaneously predict behavior and attribute basic goals to conspecifics, but it remains unclear whether, like humans, they spontaneously ascribe mental states to animated shapes. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 44 publications
2
12
2
Order By: Relevance
“…In contrast to Klein et al (2009), however, Schafroth et al (2021 did not find longer fixation duration for Frith-Happé's ToM animations in macaque monkeys. Here, we confirmed the results of Klein et al (2009) in humans, whereas marmosets, like macaques (Schafroth et al, 2021), did not show any significant difference between fixation durations in the two types of animations.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In contrast to Klein et al (2009), however, Schafroth et al (2021 did not find longer fixation duration for Frith-Happé's ToM animations in macaque monkeys. Here, we confirmed the results of Klein et al (2009) in humans, whereas marmosets, like macaques (Schafroth et al, 2021), did not show any significant difference between fixation durations in the two types of animations.…”
Section: Discussionsupporting
confidence: 89%
“…By conducting mixed analyses of variance (ANOVA), with factors of species (Human vs Marmoset) and condition (ToM vs Random animation videos), we found a significant interaction between species and condition (F(1,22)=7.67, p=.01, ηp 2 =.258). Here we observed longer fixation durations for ToM animation videos (M=317.2 ms) as compared to Random videos (M=269.0 ms) for humans (p =.029) but not for marmosets (258.3 ms vs 270.5 ms, p=.81).This finding confirms that humans fixate longer in the ToM condition (Klein et al, 2009) whereas marmosets, like macaques (Schafroth et al, 2021), do not show this effect.…”
Section: Gaze Patterns For Frith-happé's Tom and Random Animations In...supporting
confidence: 67%
See 1 more Smart Citation
“…On the other hand, midSTS interactions with the visual system in macaques might reflect stronger dependencies of TOMrelated computations on visuo-social information. This constraint might explain why macaques did not distinguish between socially and randomly interacting abstract shape as previously observed (48) despite their abilities for face pareidolia (49). These between-species differences might reflect greater specialization of TPJ in humans that may have occurred in association with the expansion and reorganization ( 16) of the temporal cortex in the hominid evolution.…”
Section: Discussionmentioning
confidence: 83%
“…Whether such animations are seen as social depends largely on the movement patterns of the agents (Castelli et al, 2000;Gao et al, 2009). This phenomenon appears to transcend age (Gordon & Roemmele, 2014;Rochat et al, 1997) and culture (Barrett et al, 2005), although interestingly, is not found in monkeys (Schafroth et al, 2021). Individuals with certain neurological or psychiatric conditionsmost notably autism-are less likely to perceive social interactions in these animations (Abell et al, 2000;Fong et al, 2017;Klin, 2000;Langdon et al, 2020) and show commensurately lower activity in typical social processing regions of the brain (Castelli, 2002;Herrington et al, 2007;Kana et al, 2009Kana et al, , 2015.…”
mentioning
confidence: 97%